2021
DOI: 10.1002/cmdc.202100278
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Conjugates of Thiosemicarbazone and Imidazole‐2‐thione Prochelators: Iron Coordination and Antiproliferative Activity

Abstract: The central role of iron in tumor progression and metastasis motivates the development of iron‐binding approaches in cancer chemotherapy. Disulfide‐based prochelators are reductively activated upon cellular uptake to liberate thiol chelators responsible for iron sequestration. Herein, a trimethyl thiosemicarbazone moiety and the imidazole‐2‐thione heterocycle are incorporated in this prochelator design. Iron binding of the corresponding tridentate chelators leads to the stabilization of a low‐spin ferric cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Conversely, the aglycone analog AAH1 and siderophore DFO, both lacking the carbohydrate moiety, presented similar toxicity in the malignant and normal cell lines. The observed antiproliferative activity of DFO (in the low micromolar range) is attributed to iron sequestration and consistent with other reported cancer cell panels. , …”
supporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, the aglycone analog AAH1 and siderophore DFO, both lacking the carbohydrate moiety, presented similar toxicity in the malignant and normal cell lines. The observed antiproliferative activity of DFO (in the low micromolar range) is attributed to iron sequestration and consistent with other reported cancer cell panels. , …”
supporting
confidence: 91%
“…The observed antiproliferative activity of DFO (in the low micromolar range) is attributed to iron sequestration and consistent with other reported cancer cell panels. 23,44 Overall, the AH1 glycoconjugates displayed antiproliferative activities similar to those of other disulfide-masked prochelators, 23,24 including thiosemicarbazone glycoconjugates, 16 and a higher selectivity toward cancer cell lines when compared to the aglycone control. Interestingly, we found that the ovarian malignant cell line A2780 was the most susceptible to all the compounds.…”
mentioning
confidence: 83%
“…25−29 Upon cellular uptake, reduction of the disulfide bond releases a tridentate thiolate chelator that coordinates iron in mammalian cells. The disulfide linkage can also be employed to connect a biomolecule, such as a monosaccharide 30,31 or albumin, 32 to improve the cancer selectivity of the constructs and enhance their therapeutic window.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Whereas thiosemicarbazone chelators derived from mercaptobenzaldehyde have so far resulted in low-spin ferric complexes, ,, the presence of a phenolic donor leads to a high-spin configuration in [Fe­(STC4– H ) 2 ] + . Interestingly, the differences in ligand field are likely small, and chelators with similar binding units exhibit spin-crossover behavior. , …”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, prochelators have been designed to act as substrates of specific enzymes, such as β-glucosidase and acetylcholinesterase (Figure b). We have developed disulfide-masked prochelators that are reductively activated in the presence of high concentrations of reduced glutathione (GSH) upon cellular uptake (Figure c). , Disulfide masks were employed in glucose , and albumin conjugates of improved selectivity and antiproliferative activity in cancer cells. Furthermore, we found that thiosemicarbazone prochelators affect the iron phenotype of tumor-associated macrophages and therefore have the potential to impact the tumor microenvironment. , …”
Section: Introductionmentioning
confidence: 99%